THE EFFECT OF POLYPROPYLENE PLASTIC RESIDUE ON HEATED PALM OIL AGAINST HISTOPATHOLOGICAL CHANGES OF SMALL INTESTINE ON MALE WHITE RAT (Rattus norvegicus) WISTAR STRAIN - Amaris, Aulia Puspa; Yustinasari, Lita Rakhma; Legowo, Djoko; Plumeriastuti, Hani; Anwar, Chairul; Hidajati, Nove (Journal of Basic Medical Veterinary, 2019)
This study was conducted to investigate the effect of polypropylene residue on heated palm oil against histopathological changes of small intestine on male white rat (Rattus norvegicus) wistar strain. Eighteen male white rats divided into three groups and were administered via peroral gavage with different treatments for five weeks. The treatment were Control (84 grams palm oil), P1 (84 grams palm oil with 2.3 grams plastic), and P2 (84 grams palm oil with 6.81 grams plastic). The histopathological changes of small intestine were examined by using Barthel Scoring method was analysed using Kruskal Wallis and continued with Mann-Whitney test. The result showed that were significant difference (p<0.05) between treatment groups. The worse damage of polypropylene plastic residue was 6.81 grams.